Omitting TMS component from paired associative stimulation with high-frequency PNS: A case series of tetraplegic patients - Pohjonen, Markus (Clin Neurophysiol Pract, 2021)
OBJECTIVES: Earlier studies have shown how chronic spinal cord injury (SCI) patients have benefitted from paired associative stimulation (PAS), consisting of high-frequency peripheral nerve stimulation (PNS) and high-intensity transcranial magnetic stimulation (TMS). Since high-frequency PNS is poorly characterized, its therapeutic effect without TMS should be evaluated. We tested the effect of PNS combined with motor imagery in chronic SCI patients using the same parameters of PNS as in earlier PAS-based studies that also used TMS. METHODS: Five patients with chronic incomplete SCI and tetraplegia received a 6-week treatment of PNS combined with motor imagery to the weaker upper limb. Patients were evaluated with Manual Muscle Testing (MMT), hand function tests (Box and block, grip and pinch strength dynamometry), and spasticity. RESULTS: There was no significant change in hand function tests or spasticity. MMT values improved significantly immediately after the PNS period (0.59 ± 0.17, p = 0.043) and in the 1-month follow-up visit (0.87 ± 0.18, p = 0.043). However, improvement of MMT values was weaker than in chronic tetraplegic patients in a corresponding PAS study that used identical PNS stimulation but also included the TMS component omitted here (Tolmacheva et al., 2019a, Clin Neurophysiol Pract). CONCLUSIONS: The lack of effect on functional hand tests with the protocol presented here suggests that the synergistic effect of PNS and TMS components is essential for the full therapeutic effect previously observed with PAS intervention. The moderate improvement of the MMT score suggests the possible usefulness of PNS and motor imagery for some of those tetraplegic SCI patients who have contraindications to TMS. SIGNIFICANCE: These results add to the understanding of the PAS therapeutic mechanism by highlighting the importance of dual stimulation for achieving the full therapeutic effect of long-term PAS with a high-frequency PNS component.